2002
DOI: 10.1095/biolreprod67.1.247
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Testis Morphometry and Seminiferous Epithelium Cycle Length in Donkeys and Mules1

Abstract: The mule (Equus mulus mulus) is a sterile hybrid domestic animal that results from the breeding of a male donkey (Equus asinus) to a female horse (Equus caballus). Usually, spermatogenesis in mules does not advance beyond spermatocytes. In the present study, we performed a comparative and more accurate morphometric and functional investigation of the testis in donkeys and mules. Due to the smaller testis size, lower seminiferous tubule volume density, and fewer germ cells, the total length of seminiferous tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
56
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 37 publications
12
56
0
3
Order By: Relevance
“…This observation is in agreement with a number of reports in the literature Neves et al, 2002;Almeida et al, 2006;Costa et al, 2008;Leal and França, 2009), suggesting that phylogeny is strongly related to stage frequencies when grouped in premeiotic and postmeiotic phases. Although the morphology of germ cells in peccaries was very similar to those described for domestic (Swierstra, 1968;França and Cardoso, 1998) and wild pigs (Almeida et al, 2006), the germ cell associations in peccaries resembled more those observed for the wild boar.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is in agreement with a number of reports in the literature Neves et al, 2002;Almeida et al, 2006;Costa et al, 2008;Leal and França, 2009), suggesting that phylogeny is strongly related to stage frequencies when grouped in premeiotic and postmeiotic phases. Although the morphology of germ cells in peccaries was very similar to those described for domestic (Swierstra, 1968;França and Cardoso, 1998) and wild pigs (Almeida et al, 2006), the germ cell associations in peccaries resembled more those observed for the wild boar.…”
Section: Discussionsupporting
confidence: 93%
“…The total duration of spermatogenesis took into account that approximately 4.5 cycles are necessary for this process to be completed from type A spermatogonia to spermiation (Amann and Schanbacher, 1983). Because primary spermatocytes' nuclear volume grows markedly during meiotic prophase (França et al, 1995;Neves et al, 2002;Leal and França, 2006), the size of their nuclei was used to determine more precisely the location of the most advanced labeled germ cell, particularly when these cells were present in stages showing high frequency.…”
Section: Length Of the Seminiferous Epithelium Cyclementioning
confidence: 99%
“…The similarity in the seminiferous epithelium cycle shared by A. lituratus, A. planirostris, C. perspicillata, P. lineatus and S. lilium has also been observed in other mammalian species such as the puma (Guiã o-Leite et al, 2006), wolf (Bitencourt et al, 2007) and donkey (Neves et al, 2002).…”
Section: Discussionmentioning
confidence: 62%
“…The seminiferous tubules seem to exert some poorly understood effects on Leydig cell structure and steroidogenic activity (Parvinen 1982). Moreover, macrophages that are present in the testis intertubular tissue have been suggested to enhance Leydig cell steroidogenic activity in vitro (Neaves et al 2002). It has also been stated that a testicular luteinizing hormone releasing hormone-like factor probably secreted by the Sertoli cells has the potential to exert a wide range of stimulatory and inhibitory effects on Leydig cell function (Sharpe 1984).…”
Section: Introductionmentioning
confidence: 99%